OPTIMALISASI PROSES PRODUKSI DENGAN MENGGUNAKAN METODE OVERALL EQUIPMENT EFFECTIVENESS: (Survey pada PT. Arteria Daya Mulia Kota Cirebon) - Suci Hastary; Ayus ahmad Yusuf; Robi Awaludin (Jurnal Bina Bangsa Ekonomika, 2021)
High equipment maintenance cost in a company is caused by inappropriate improvement. Overall Equipment Effectiveness (OEE) is one of methods that can provide information to identify and clarify the cause of low performance of an equipment, that can solve the problems. This study aims to identify machine productivity, that analyze problems that cause losses. There are three main factors in OEE calculation, namely availability, performance, and quality. The average achievement value of OEE in PT. Arteria Daya Mulia of 74.32% can be concluded that the average value of OEE is still below the standard of Japan Institute of Plan Maintenance (JIPM) of 85% (Nakajima, 1988). Based on the calculation using Six Big Losses, the factor that caused the decreasing effectiveness of the most dominant machine was the Idling and Minor Stoppages factor of 21.54%, so that it was a top priority to make improvements as an initial step in efforts to increase the productivity and efficiency of the netting machine.